Transposition of the Escherichia coli insertion element gamma generates a five-base-pair repeat. - Reed, R R (1979)
We have determined DNA sequences surrounding the termini of the Escherichia coli insertion element gamma delta, both at its normal locus on the F (fertility) factor and at three different sites of insertion into the plasmid pBR322. After transposition, a five-base-pair pBR322 sequence is duplicated and appears in direct orientation adjacent to each end of the element. No such duplication flanks the ends of gamma delta in F, and there is no apparent homology between the sequences surrounding gamma delta in F and the five-base-pair duplications generated by insertion. These findings suggest that the duplications are not essential for transposition and that they do not act to direct gamma delta to a homologous site in the target chromosome. In addition, we find that the 35-base-pair inverted repeat that comprises the termini of gamma delta is strikingly similar in sequence to the ends of both the ampicillin-resistance transposon Tn3 and a 200-nucleotide-long sequence on the plasmid pSC101 which has been shown to mediate recombination with phage f1 replicative form. Within the terminal region, there is a specific heptanucleotide sequence common to each of the above elements and to bacteriophage Mu, all of which generate five-base-pair repeats upon insertion.